2018
DOI: 10.1007/s00330-017-5185-1
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical changes in MRI-determined right ventricular volumes and function in subjects with prediabetes and diabetes

Abstract: • MRI was used to detect subclinical changes in right ventricular parameters. • Diabetes mellitus is associated with right ventricular dysfunction. • Impairment of right ventricular volumes seems to occur predominantly in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In recent decades, cardiac magnetic resonance (CMR) imaging has been commonly used in clinical practice, which can provide various characteristics of cardiac structure and myocardial tissue [8][9][10][11][12][13]. More specifically, feature tracking and first-pass perfusion of CMR imaging have been used to measure myocardial deformation and to detect microvascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, cardiac magnetic resonance (CMR) imaging has been commonly used in clinical practice, which can provide various characteristics of cardiac structure and myocardial tissue [8][9][10][11][12][13]. More specifically, feature tracking and first-pass perfusion of CMR imaging have been used to measure myocardial deformation and to detect microvascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there is a paucity of information on how SGLT2 inhibition affects the morphology and function of the RV [ 29 ]. This is surprising given that individuals with T2DM may have impaired RV systolic and diastolic function as well as decreased RV volumes, even in the absence of established coronary artery disease or HF [ 19 , 21 , 30 , 31 ]. Furthermore, T2DM is associated with RV systolic and diastolic dysfunction in the setting of HF with preserved LVEF, independent of RV afterload [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…cMRI provides the reference standard assessment of right ventricular (RV) structure and function [ 14 ], which are prognostic markers in various clinical settings including ischemic cardiomyopathy [ 15 ], non-ischemic cardiomyopathy [ 16 ], HF [ 17 ] and a multiethnic population free of CV disease [ 18 ]. T2DM affects RV remodeling, systolic and diastolic function, even in the setting of preserved LV ejection fraction (LVEF) [ 19 21 ]. Furthermore, T2DM is associated with RV dysfunction following ST elevation myocardial infarction [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Patschneider et al showed that DM as well as prediabetes is associated with decreased RV endsystolic and enddiastolic volumes as well as stroke volumes, indicative of early-onset RV impairment prior to symptom onset. (17,18). Posttranslational modi cation (O-linked ß-N-acetylglucosamine modi cation) in DM patients may have contributed to changes in calcium sensitivity, which is a measure of impaired contractile force development.…”
Section: Discussionmentioning
confidence: 99%